Engagement of a parieto-cerebellar network in prism adaptation. A double-blind high-definition transcranial direct current stimulation study on healthy individuals. (January 2022) - Panico, Francesco; Sagliano, Laura; Sorbino, Gaia; Trojano, Luigi
Abstract: Prism Adaptation (PA) is a non-invasive method to investigate visuomotor control. Recent neurostimulation studies have proposed an interpretation of the mechanisms underlying PA based on functioning of brain networks, instead of focusing on single brain areas. To test the functioning of the network during a classical PA procedure, here we used for the first time High-Definition transcranial Direct Current Stimulation (HD-tDCS) to simultaneously inhibit or facilitate brain activity in two main nodes of the network, namely the parietal cortex and the cerebellum, in healthy individuals. The main results showed that simultaneous anodal HD-tDCS over the two regions reduced terminal errors during exposure to prism glasses as compared to cathodal and sham stimulation. Conversely, cathodal HD-tDCS reduced after-effect as compared to anodal and sham stimulation following prism removal. Overall, these results provide new insights on the network related to the deployment of PA mechanisms and demonstrate the feasibility of using non-invasive HD-tDCS to modulate the adaptive mechanisms of PA.